Extraction of Oil Heteroatomic Compounds Using Metal Powders; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Golushkova E. B. Evgeniya Borisovna (Chemical Engineering and Technology, 2016)
Title screen